Improving attrition resistance of oxygen carriers by biomass ash in chemical looping process. (15th August 2023) - Yang, Li; Chen, Wenbin; Song, Chen; Li, Caifu; Chen, Jinlong; Zhang, Xi; Liu, Fang
Graphical abstract: Highlights: Three biomass ash on the performance of red mud oxygen carrier were studied. A potential method to improve the attrition resistance of OCs was proposed. Fiber structure was identified in corn straw ash-modified red mud oxygen carrier. Mechanism of fiber structure on the improvement of attrition resistance was studied. Abstract: Chemical looping combustion (CLC) relies on cyclic circulation of oxygen carriers (OCs) between fuel reactor and air reactor to transfer lattice oxygen and heat. OCs' attrition is an important issue hindering large scale application of CLC technology. Attrition is caused by cracks and abrasion, and method to stop crack propagation is an effective way to mitigate attrition. Biomass ash contains inert and alkali metal components, and it may have the potential to increase the reactivity and reinforce the skeleton structure of OCs. The effects of rape straw ash, corn straw ash and bagasse ash on the reactivity, cumulative attrition rate of red mud OCs were evaluated, and their effects on skeleton structure were analyzed, and finally, the strengthening mechanism of OCs skeleton structure was proposed. The results showed that the rape straw ash rich in K and Ca components promoted the reactivity of OCs. Although the Si-rich bagasse ash decreased the reactivity of OCs, it improved the attrition resistance of OCs. Corn straw ash rich in K and Si components was an effective skeleton strengthening material, which improved both the reactivity and the attrition resistance. The cumulative attrition rate of red mud was 2.74%, and the cumulative attrition rate of CSA sample was 0.35%, which was 87.32% lower than that of OC sample, indicating fine attrition resistance. The fiber structure could strengthen the skeleton of OC, therefore, decreasing attrition rate.